An index for the assessment of degraded Mediterranean forest ecosystems - Modica, Giuseppe; Merlino, Angelo; Solano, Francesco; Mercurio, Roberto (Forest Systems, 2015)
Aim of study: Diagnosing the degradation degree of forest ecosystems is the basis for restoration strategies. However, there is no literature documenting how to quantify the forest degradation degree by using synthetic indicators, also because there is not a widely accepted definition for "forest degradation" and "degraded forest". Although there are many definitions of forest degradation that converge on the loss of ecosystem services, still today there are no largely accepted methods that give operational guidance to help in defining it. In the present research, with the aim to assess the degree of forest degradation, an integrated index - FDI, Forest Degradation Index - was developed. Area of study: In this first application, the FDI was applied and validated at stand level in two different Mediterranean forest types in two different case studies: Madonie and Nedrodi regional Parks (Sicily, Italy). The first dominated by sessile oak [Quercus petraea (Matt.) Liebl. subsp. austrotyrrhenica Brullo, Guarino & Siracusa], the second dominated by cork oak (Quercus suber L.). Material and methods: FDI is a synthetic index structured starting from representative and relatively easily detectable parameters. Here, we propose a set of six indicators that should be assessed to determine the forest degradation: Structural Index (SI), Canopy Cover (CC), Natural Regeneration Density (NRD), Focal Species of Degradation (FSD), Coarse Woody Debris (CWD), and Soil Depth (SD). FDI, here proposed and discussed, has been based on a MCDA (Multi-Criteria Decision Analysis) approach using the Analytic Hierarchy Process (AHP) technique, and implemented in order to contribute in finding simple indicators useful for forest restoration purposes that have an eco-functional basis. Main results: An integrated index of forest degradation has been defined. FDI values are comprised in the closed interval [0, 10], ranging from class I (Higher ecological functionality) to class IV (Lower ecological functionality). A forest fallen in the FDI-IV class can be defined degraded. In this first application, degradation occurs in SA-4 and in SB-4 where the lowest values (qualitative and quantitative) of the indicators were recorded and the FDI reach the minimum value. Research highlights: FDI has proved to be a useful tool at stand level in identifying a threshold value below which a forest can be termed as ‘degraded’. In turn, FDI assumes the meaning of descriptor of the ecological functionality. Future development of the FDI will provide an extension of the application at landscape scale exploiting the potential advantages in coupling MCDA and GIS (Geographical Information Systems) techniques. Keywords: Forest Degradation Index (FDI); Sustainable Forest Management (SFM); Mediterranean Forest Landscape; Multi-Criteria Decision Analysis (MCDA) approach; Analytic Hierarchy Process (AHP).